The Impact of Staff Meetings on Supervision at the University of Education, Winneba - Anyan, Jerry Addison (Ghana Journal of Higher Education Management, 2024)
Forty-eight junior and senior staff from faculties, departments and sections of the University of Education, Winneba were sampled to find out whether staff meetings were being held with them in their respective offices and whether it impacted on their work performance. The main instrument used was interview. The results showed that staff meetings were not being held with senior and junior staff in most offices and its absence affected the discharge of their work. A number of recommendations have been made to address the situation.